Proteolytic and angiotensin‐converting enzyme‐inhibitory activities of selected probiotic bacteria. (28th February 2016) - Ahtesh, Fatah B.; Stojanovska, Lily; Mathai, Michael L.; Apostolopoulos, Vasso; Mishra, Vijay K.
Summary: This study was carried out to examine the proteolytic and angiotensin‐converting enzyme (ACE‐I) activities of probiotic lactic acid bacteria (LAB) as influenced by the type of media, fermentation time, strain type and media supplementation with a proteolytic enzyme (Flavourzyme ® ). Lactobacillus casei (Lc210), Bifidobacterium animalis ssp12 (Bb12), Lactobacillus delbrueckii subsp. bulgaricus (Lb11842) and Lactobacillus acidophilus (La2410) were grown in 12% of reconstituted skim milk (RSM) or 4% of whey protein concentrates (WPC‐35) with or without combination (0.14%) of Flavourzyme ® for 12 h at 37 °C. All the strains were able to grow in both media depending on type of strains used and fermentation time. All the strains showed higher proteolytic activity and produced more antihypersensitive peptides when grown in RSM medium at 12 h, when compared to WPC. Combination with Flavourzyme ® also increased LAB growth and proteolytic and ACE‐I activities. Of the four strains used, Bb12 and La2410 outperformed Lc210 and Lb11842 . The highest ACE‐I activity and proteolytic activity were found in B. animalis ssp12 combined with Flavourzyme ® . Flavourzyme ® led to an increase in the production of bioactive peptides with ACE‐I activity during 12 h at 37 °C. Abstract : Peptide profile of whey protein concentrate with Lactobacillus casei (Lc210), Bifidobacterium animalis ssp12 (Bb12), Lactobacillus delbrueckii subsp. bulgaricus (Lb11842) and Lactobacillus acidophilus (La2410) at 37 ?C for 12 h, combined with Flavourzyme.